2021
DOI: 10.1039/d1ra00271f
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured RuO2–Co3O4@RuCo-EO with low Ru loading as a high-efficiency electrochemical oxygen evolution catalyst

Abstract: The optimized RuO2/Co3O4–RuCo-EO electrode with Ru loading of 0.064 mg cm−2 exhibits the excellent oxygen evolution activity with an overpotential of 220 mV at the current density of 10 mA cm−2 and a Tafel slope of 59.9 mV dec−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Fig. 8f summarizes the performance of the EG30 prepared in this study compared to the NiO/Ni/C 8–10,38–44 and noble metal 45,46 previously reported in literature. Herein, we mainly compare overpotentials and Tafel slopes.…”
Section: Resultsmentioning
confidence: 94%
“…Fig. 8f summarizes the performance of the EG30 prepared in this study compared to the NiO/Ni/C 8–10,38–44 and noble metal 45,46 previously reported in literature. Herein, we mainly compare overpotentials and Tafel slopes.…”
Section: Resultsmentioning
confidence: 94%
“…The optimized RuO 2 /Co 3 O 4 −RuCo/EO electrode ensured good electrocatalytic activity. 185 Also, Sarkar et al have created a pH universal HER catalyst via the pyrolysis technique to produce a Ru-adorned hollow N-doped carbon matrix (Ru@ NCN). Due to the M−S effect, the electrons transferred from the metal/semiconductor (Ru/NCN) heterojunction exhibited overpotentials of 36, 49, and 76 mV with a current density of 10 mA cm −2 in alkaline, acidic, and neutral environments, respectively.…”
Section: Metal−metal Nitridesmentioning
confidence: 99%
“…The M–S effect, a charge transfer process, can be beneficially utilized by the combined electrocatalysts of metal and semiconductor with a low η10 of 220 mV and a Tafel slope of 59.9 mV dec –1 for OER at a current density of 10 mA cm –2 . The optimized RuO 2 /Co 3 O 4 –RuCo/EO electrode ensured good electrocatalytic activity . Also, Sarkar et al have created a pH universal HER catalyst via the pyrolysis technique to produce a Ru-adorned hollow N-doped carbon matrix (Ru@NCN).…”
Section: Construction and Electrocatalytic Performance Of M–s Heteros...mentioning
confidence: 99%
“…12 Cobalt oxides (CoO x ) present high catalytic activity for OER in alkaline solution, especially the Co 3 O 4 spinel that has been widely investigated as an attractive anode material with high activity, corrosion resistance in alkaline electrolytes, excellent redox property originating from its Co 2+ /Co 3+ mixed valence nature. 1,3,5,6,[13][14][15] Furthermore, the development of acid-stable OER electrocatalysts is still a challenge. 5 The electrolyte pH has a signicant impact on the choice of the electrocatalyst, for instance, for the application of proton exchange membrane (PEM) electrolyzer for hydrogen production at acid pH, active and resistant catalysts are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The development of efficient technologies for the conversion and storage of energy using renewable sources has been intensified, especially those related to the use of solar energy. 1 However, some factors hamper the implementation of a solar-based generation system, such as the intermittence of sunlight and the high cost of silicon cells. These barriers make even more urgent the search for new materials to play the different functions in an artificial leaf device, such as light-harvesting, electron conduction, and hydrogen/oxygen catalytic generation from the water splitting reaction.…”
Section: Introductionmentioning
confidence: 99%